Effect of non-zero mean stress bending-torsion fatigue on fracture surface parameters of 34CrNiMo6 steel notched bars - Macek, Wojciech (2020)
Modern methods of testing materials require the use of the latest technologies and combining meas-urement and calculation methods. It is important to find a quantitative way of describing, among other things, the failures so that it can help to design with high accuracy. This paper studies loading orien-tations on crack shape and fracture surface changes. The advantage of the entire fracture surface method is simplicity and applicability in studies on other materials, shapes and loadings. A higher values of fracture surface parameters (Sx, Vx) was observed in failure specimens with lower σ/τ (B/T) ratios. It has been observed that largest crack lengths with a small number of cycles occur for loading combinations different then B=T. As well as analyzed surface parameters Sx, Vx, are higher for larger number of cycles to crack initiation (Ni) values.